Analysis of the helminth community of Notothenia coriiceps (Actinopterygii: Nototheniidae) collected in the water area of the Argentine Islands, West Antarctica - Kuzmina, T.; Kuzmin, Yu.; Salganskiy, O.; Lisitsyna, O.; Korol, E. (Ukrainian Antarctic Journal, 2022)
Helminth community of the Antarctic black rockcod, Notothenia coriiceps, was examined using the fish samples collected in 2014—2015 (106 specimens) and 2020—2021 (78 specimens) in the water area of the Argentine Islands, West Antarctica. In total, 30,951 helminth specimens were collected and identified. We analyse the helminth infra- and component communities and investigate possible changes in the main parameters of helminth communities of N. coriiceps during the six-year period. Thirty species of helminths from five taxonomic groups were recorded: one species of Monogenea, 5 of Nematoda, 4 of Cestoda, 9 of Trematoda, and 11 of Acanthocephala. Notothenia coriiceps was found to be the definitive host of 18 helminth species; 12 species parasitize it in the larval stage using N. coriiceps as the second intermediate or paratenic host. The proportion of larval helminths in the samples was lower in 2014—2015 (73.4%) than in 2020—2021 (81.4%). The number of dominant helminth species (infection prevalence >50%) increased from seven in 2014—2015 to nine in 2020—2021. In helminth infracommunities, the species richness was similar in two samples. On the other hand, we found significantly higher helminth abundance in the infracommunities from the sample collected in 2020—2021. In the helminth component community, the diversity indices (Shannon, Simpson, Pielou, Berger-Parker) evidenced higher evenness and lower domination in the sample collected in 2014—2015 compared to the sample collected in 2020—2021. Lower evenness in 2020—2021 was due to the larger relative abundance of larval Pseudoterranova sp. and Corynosoma spp. We suggest a deeper investigation of the role of separate helminth species in the component community changes, as well as further monitoring of component community parameters as prospective directions for future studies of helminth communities of N. coriiceps in West Antarctica.